THE EFFECT OF GIVING EXERCISE THERAPY WITH THE MCKENZIE METHOD IN THE ELDERLY TO REDUCE THE PAIN OF HERNIA NUCLEUS PULPOSUS (HNP) - Yoel Kristian Adi Candra; Daniel Saka Pratama; Deasy Virka Sari (Physiotherapy and Physical Rehabilitation Journal, 2022)
Background : Hernia Nucleus Pulposus (HNP) is a state when the nucleus pulposus go out stand out then push to direction canal spinalis through annulus torn fibrosus. HNP often occur on area lumbar 4 - 2 lumbar 5 and lumbar 5 - sacrum 1. Pain in HNP due to by pathological processes in the column vertebral on discus intervertebral. By because that, from a number of the research that we get, giving therapy McKenzie workout effective in reduce pain Hernia Nucleus Pulposus (HNP). Research Objective: To find out influence give therapy McKenzie's workout against Hernia Nucleus Pulposus Condition. Methodology : Overview systematic from three related articles with give therapy McKenzie training on Hernia Nucleus Pulposus Condition. Results : Therapy practice with McKenzie method can give significant effect to reduce painful on Hernia Nucleus Pulposus Condition. Conclusion : Giving therapy practice with McKenzie method is able give influence reduce pain due to a herniated nucleus pulposus .